Policy dimension for promoting inter and intra‑varietal diversity and evolutionary crop populations - Joshi, Bal Krishna; Neupane, Shree Prasad; Gauchan, Devendra; Ajaya, Karkee; Dipendra, Ayer Kumar; Mengistu, Dejene Kassahun (Springer, 2024)
The value of broad genetic base cultivars is often underestimated in the formal seed system, which primarily emphasizes uniform, monogenotyped varieties to ensure food security. To gather insights on the significance of farmer’s varieties, cultivar mixtures, and evolutionary populations, a comprehensive approach involving surveys, focus group discussions, interviews, field observation and literature reviews was undertaken. Current legal frameworks in seed systems and variety handling predominantly serve the interests of seed companies, breeders, and extension officials, with limited consideration for the needs and preferences of farmers. This results in farmer’s varieties, characterized by their high genetic variation, as well as cultivar mixtures and evolutionary populations, receiving limited support within the policy framework. These broad genetic base cultivars have been cultivated and preserved by farmers for generations and exhibit resilience to diverse environmental conditions. The formal seed system, which has gained prominence, has separated farmers from a crucial aspect of their agricultural heritage. It is now managed by government offices and private seed companies, necessitating financial contributions from farmers to participate in the seed system. To encourage the cultivation of site-specific varieties with substantial genetic diversity, there is a need to promote these varieties, whether registered or unregistered, through a legal framework that encompasses all agricultural produces, not solely seeds. Such a framework acknowledges the capacity of farmers to independently maintain and cultivate their seeds, contributing to the preservation of genetic diversity and sustainable agriculture.